An Evaluation of Health Rocks! with a Control Group - Dan Wang; Yunqi Wang; Maria R. de Guzman; Yan R. Xia; Kieu-Anh T. Do; Zhenqiao Yang (Journal of Human Sciences and Extension)
Youth substance use challenges their health and well-being. There is research and practical need for rigorous evaluation of substance use prevention programs in prompting positive youth development. This study examined the program effectiveness of Health Rocks!, a youth substance use prevention program, with a quasi-experimental two-factor mixed evaluation design. We gathered data from 584 participants (i.e., 475 youth in the treatment group and 109 youth in the control group) and conducted paired-sample t-tests for each group to compare youth substance use-related outcomes before and after the training. Results showed that youth in the treatment group reported significant increases in substance use knowledge, perceived support, and assets to make healthy life decisions, whereas the youth in the control group showed no significant differences in these outcomes. These findings, consistent with previous evaluations, highlight program effectiveness and the continued use of post-then-pre-evaluations in practice.